Physiological and biochemical evaluation of high anthocyanin pigmented tea (Camellia sinensis L. O. Kuntze) germplasm for purple tea production - Patel, Pradeep Kumar; Siddiqui, Shahida Anusha; Kuča, Kamil; Sabhapondit, Santanu; Sarma, Rupak; Gogoi, Boby; Singh, Shobhit Kumar; Bordoloi, Ranjeet Kumar; Saikia, Jayanta Kumar; Gogoi, Romen Chandra; Bhardwaj, Kanchan; Yang, Jie; et al. (Frontiers in Nutrition, 2022)
Finding promising purple tea germplasm that would target new tea products for diversification and value addition boost the tea industry's economic growth. Accordingly, ten tea germplasm viz. TRA St. 817, TRA St. 293, TRA St. 400, TRA 177/3, TRA 376/2, TRA 376/3, TRA 427/7, TRA P7, TRA P8 and TV1 were evaluated in terms of gas exchange parameters, multiplication performance, and biochemical markers such as chlorophyll, carotenoids, and anthocyanin content, which are related to the purple tea quality. The investigated gas exchange and biochemical parameters revealed significant differences. Germplasm TRA St.817 was physiologically more efficient (24.7 µmol m-2 s-1), followed by TRA St. 293, exhibiting the highest net photosynthesis, water use efficiency (19.02 µmol mmol-1), carboxylation efficiency (0.73), chlorophyll fluorescence or photochemical efficiency of PSII (0.754) and mesophyll efficiency (ci/gs ratio: 2.54). Net photosynthesis was positively correlated with water use efficiency, carboxylation efficiency, mesophyll efficiency, and photochemical efficiency of PSII (r=0.965**, 0.937**, 0.857**, 0.867**; P=0.05), respectively, but negatively correlated with the transpiration ratio (r=-0.878**; P=0.05) based on Pearson correlation analysis. The total anthocyanin content (4764.19 µg.g-1 fresh leaf weight) and carotenoid content (3.825 mg.g-1 fresh leaf weight) were highest in the TRA St.817 germplasm, followed by germplasm TRA St. 293 (2926.18 µg.g-1 FW). In contrast, total chlorophyll content was significantly low (1.779 mg.g-1 fresh weight), which is very suitable for manufacturing purple tea. The highest carotenoid concentration in TRA St. 817 was 3.825 mg.g-1 FW, followed by TRA P8 (3.475 mg.g-1 FW), favouring the formation of more volatile flavor constituents. The promising germplasm, TRA St 817, has a multiplication success rate of 91.4 % through cleft grafting. The outcome reveals that TRA St.817 is a promising germplasm that can be used to make speciality teas, i.e. purple tea.